Implementasi Peraturan Daerah Kabupaten Banyumas Nomor 19 Tahun 2014Tentang Perlindungan dan Pelayanan Bagi Penyandang Disabilitas (KhususnyaPemenuhan Hak Kesehatan Terhadap Penyandang Disabilitas Ganda) - Ida Arifatul Khasanah; Esti Ningrum; Agoes Djatmiko (Wijayakusuma Law Review, 2023)
This study aims to find out the implementation of Banyumas Regency Regional Regulation Number 19 of 2014concerning Protection and Services for Persons with Disabilities (Especially the Protection and Fulfillment of HealthRights for Persons with Multiple Disabilities), and to find out the obstacles faced in the implementation of thefulfillment of the right to Health for persons with multiple disabilities. This research uses sociological juridicalresearch methods. The collection of research data was carried out by means of field interviews and observationssupported by literature studies. Data analysis in this study is descriptive qualitative. Based on the results of researchand discussion, it can be concluded that Iimplementation of Banyumas Regency Regional Regulation Number 19 of2014 concerning Protection and Services for Persons with Disabilities (Especially Protection and Fulfillment ofHealth Rights for Persons with Multiple Disabilities) has been implemented by The Banyumas Social and Communityand Village Empowerment Office (Dinsospermasdes) with the existence of social rehabilitation and communityparticipation of the Paguyuban Peduli Disabiltas Ganda (PPDG) through its work program that handles 95 peoplewith multiple disabilities with a percentage of 11% of the number of people with multiple disabilities in BanyumasRegency. In the implementation of the fulfillment of health rights, there are obstacles that must be faced, namely thelimited professional or competent human resources owned, data on persons with disabilities in Banyumas Regencyhave not been updated thoroughly, the limited budget available for the implementation of the fulfillment of the rightto k health of persons with disabilities, lack of family awareness of the rights of persons with disabilities due toshame and they prefer to hide their children, limited access to information from and for people with disabilities